2015
DOI: 10.1021/ma501662r
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Microporous Polyimides Based on Perylene and Triazine for Highly CO2-Selective Carbon Materials

Abstract: Carbon dioxide (CO 2 ) capture from point sources like coalfired power plants is a potential solution for stabilizing atmospheric CO 2 content to avoid global warming. Sorbents with high and reversible CO 2 uptake, high CO 2 selectivity, good chemical and thermal stability, and low cost are desired for the separation of CO 2 from N 2 in flue or natural gas. We report here, for the first time, on the synthesis of new microporous polyimide (PI) networks from the condensation of perylene-3,4,9,10-tetracarboxylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
102
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(104 citation statements)
references
References 82 publications
2
102
0
Order By: Relevance
“…426,427 Hupp and co-workers exploited the carboxylate substituents of ditopic 5-10c (Chart 25) for the fabrication of a Zn 2+ -based metal−organic framework that exhibits a N 2 -accessible surface area of 430 m 2 /g (after activation with hypercritical carbon dioxide) similarly to recently published microporous polyimide networks, which feature a remarkable selectivity for CO 2 adsorption, however. 428, 429 The final structural evidence for the aforementioned material still has to be rendered because no single crystals suitable for X-ray structural determination could be grown. In a complementary approach, Bein and co-workers reported on the subsequent pore surface functionalization of a Cr 3+ -based MOF by incorporating the Lewis basic monotopic PBI ligand 5-10d (Chart 25) into the coordinatively unsaturated Lewis acidic metal organic framework.…”
Section: Metallosupramolecular Polyhedramentioning
confidence: 99%
“…426,427 Hupp and co-workers exploited the carboxylate substituents of ditopic 5-10c (Chart 25) for the fabrication of a Zn 2+ -based metal−organic framework that exhibits a N 2 -accessible surface area of 430 m 2 /g (after activation with hypercritical carbon dioxide) similarly to recently published microporous polyimide networks, which feature a remarkable selectivity for CO 2 adsorption, however. 428, 429 The final structural evidence for the aforementioned material still has to be rendered because no single crystals suitable for X-ray structural determination could be grown. In a complementary approach, Bein and co-workers reported on the subsequent pore surface functionalization of a Cr 3+ -based MOF by incorporating the Lewis basic monotopic PBI ligand 5-10d (Chart 25) into the coordinatively unsaturated Lewis acidic metal organic framework.…”
Section: Metallosupramolecular Polyhedramentioning
confidence: 99%
“…Synthetic protocols which can be used for the generation of microporous polymers are highly diverse and range from metalcatalyzed or -mediated (Sonogashira, 4,5 Suzuki, 6 Yamamoto, 7 Buchwald-Hartwig, 8 Eglinton, 9 Heck 10 ) to click-type reactions, 11 acid or base-catalyzed polycondensation reactions (formation of polyamides, 12 -imides, [13][14][15] -benzimidazoles, 16,17 -dioxanes, 18 -boroxines and boronate esters, 19 -imines 20 -aminals, 22 azo-bridged compounds [23][24][25] and many others [26][27][28][29] The great variety of synthesis conditions not only allows the usage of differentially functionalized monomers, but much more importantly to find appropriate reaction conditions tolerating any given functional group which is planned to be introduced into the network, i.e. synthesis can be carried out with high chemical orthogonality.…”
Section: Synthesis and Structurementioning
confidence: 99%
“…More courage in using microporous polymers at really challenging catalytic conditions would therefore be desirable. In this respect it is important to note that it has been frequently reported that thermal or oxidation stabilities of microporous polymer networks can be enhanced, for example by increasing the cross-linking density 38 or introducing inorganic building blocks 84,85 or heteroatoms 15,86,87 into the frameworks.…”
mentioning
confidence: 99%
“…In recent years, many amine functionalized or nitrogen-rich porous materials were found to show good CO 2 adsorption properties because of the existence of strong interactions between the nitrogen functionality and CO 2 molecules [21][22][23][24][25][26][27]. Among them, the porous melamine-formaldehyde resins (PMFRs) have gained great attention because they can be produced by low-cost highly abundant melamine that has suitable alkalescence (pKa = 5.5) versatile reactivity [28][29][30]. In addition, it is a mass produced product in the chemical industry and can be used as crosslinker in organic coating and plastic [31][32][33].…”
Section: Introductionmentioning
confidence: 99%